Mechanical behavior of materials - Courtney, Thomas H. (Singapore : McGraw Hill Education (Asia), 2000)
Covers principles of the mechanical behaviour of materials. Focuses on the relationship between macroscopic properties, material microstructure and fundamental concepts of bonding and crystal structure.
Includes bibliographical references and indexes.
Keywords: Materials -- Mechanical properties